Critical intervention points for European adaptation to cascading climate change impacts - Auer, Cornelia; Reyer, Christopher P.O.; Adamczak, Weronika; Aylett, Chris; Benzie, Magnus; Berndt, Jan Philipp; Bresch, David N.; Bosello, Francesco; Bressan, Giacomo; Carter, Timothy R.; Croft, Simon; Delpiazzo, Elisa; et al. (Nature Climate Change, 2025)
In an interconnected world, climate change impacts can cascade across sectors and regions, creating systemic risks. Here we analyse cascading climate change impacts on the EU, originating from outside the region, and identify critical intervention points for adaptation. Using network analysis, we integrate stakeholder-co-produced impact chains with quantitative data for 102 countries across foreign policy, human security, trade and finance. Our archetypal impact cascade model reveals critical intervention points related to water, livelihoods, agriculture, infrastructure and economy, and violent conflict. Livelihood instability, with violence exacerbating conditions in conflict-prone regions, tends to amplify risks of cascading impacts emerging from low-income countries. High-income countries can trigger cascading impacts through, for example, reduced crop exports. Our findings highlight the importance of policy coherence in addressing interconnected vulnerabilities rather than isolated risks. Thus, agricultural intensification without integrated water management may exacerbate scarcity, whereas safeguarding livelihoods alleviates cascading risks related to forced migration, violent conflict and instability.
Publisher Copyright: © The Author(s) 2025.